MENDIDIK ANAK DENGAN CINTA: ANALISIS POLA ASUH IBNU QOYYIM DAN MUHAMMAD FAUZIL ADHIM TERHADAP KESEHATAN MENTAL - Lusiana Dwi Puspita; Khodijah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The positive involvement of parents in the education of their children plays a crucial role in significantly influencing children's mental health. Ibnu Qoyyim and Muhammad Fauzil Adhim propose practical frameworks for parenting that center on love, exemplary behavior, and the This paper presents an analytical overview of how the parenting models advocated by these scholars contribute to the positive and resilient development of children's mental health. The research adopts a qualitative approach through a comprehensive literature review. The findings indicate that the parenting strategies suggested by Ibnu Qoyyim and Muhammad Fauzil Adhim strongly emphasize the importance of emotional communication, spiritual role modeling, and the provision of gentle yet firm guidance. Such approaches indirectly foster a sense of security, enhance self-confidence, and reinforce the character development of children.